The effectiveness of tobacco taxation on university students : an empirical study on Singapore’s February 2018 tax hike - Lim, Eugenia Hui Jie (Nanyang Technological University, 2020)
Taxes are part of Singapore’s multi-pronged approach in curbing cigarette consumption. Becker and Murphy’s Rational Addiction Model implied that taxes are effective in curbing cigarette consumption among younger individuals. This paper seeks to test the empirical validity of this implication on university students in Singapore by examining Singapore’s February 2018 tobacco tax hike. Multinomial logistic regression was conducted and subsequently found that at a 1% significance level, the average probability of an individual decreasing his cigarette consumption increases by 35.2% when faced with a tax hike. This shows that the increase in tax was effective in decreasing cigarette consumption among university students. Robustness checks confirmed the consistency of tax in our model. The results obtained highlight potential policy implications for the Singapore government to decrease smoking prevalence among university students.